Highly selective oxidation of organic contaminants in the RuIII-activated peroxymonosulfate process: The dominance of RuVO species. (December 2021) - Zong, Yang; Zhang, Hua; Zhang, Xiaomeng; Shao, Yufei; Zeng, Yunqiao; Ji, Wenjie; Xu, Longqian; Wu, Deli
Abstract: Ruthenium (Ru III )-activated peroxymonosulfate (the Ru III /PMS process) is one of the most efficient PMS-based advanced oxidation processes for the abatement of organic contaminants. Here we interestingly found that phenyl methyl sulfoxide (PMSO) was significantly oxidized to phenyl methyl sulfone (PMSO2 ) in the Ru III /PMS process at the pH range of 3.0–6.0, with the conversion ratio of ΔPMSO to ΔPMSO2 was close to 100%, which favored the dominance of high-valent ruthenium-oxo species (Ru V O) instead of the widely-recognized radicals (i.e, hydroxyl radical and sulfate radical). Scavenging experiments further indicated that Ru V O was unreactive to tert -butyl alcohol, but could be scavenged by methanol and dimethyl sulfoxide. Besides, sulfamethoxazole, acetaminophen, carbamazepine, diclofenac, 2, 4, 6-trichlorophenol were readily degraded in the Ru III /PMS process, but atrazine, ibuprofen, benzoic acid and 4-nitrobenzoic acid were barely removed, suggesting the high selectivity of Ru V O species. This study enriched the understandings on the mechanism of Ru III -mediated PMS activation and the nature of Ru V O species. Graphical abstract: Image 1 Highlights: Ru V O is proposed as the dominant reactive species in the Ru III /PMS process. The contribution of radical species is negligible. Ru V O species is highly selective towards electron-rich organics. Ru V O species is inert to the inhibition of coexisting anions and humic acid.